TO PUNISH OR TO PROTECT: THE ROLE OF THE PUBLIC DEFENDER’S OFFICE IN THE CRIMINAL ENFORCEMENT OF HOMELESS INDIVIDUALS - da Silva, Maria Inês Ferreira; de Souza, Sidioney Miguel; Camarão, Guajarina do Socorro Carmo de Sousa; Cardoso, Eliney Alessandro Vieira; Nazário, Kaio Henrique Rodrigues; Barbosa, Graciete Nascimento; da Silva, Eliane do Socorro Ferreira; da Silva, Regiane de Paula Ferreira; dos Santos, Regina Célia Nascimento; da Silva, Ana Cláudia Ferreira (Seven Editora, 2026)
This article aims to discuss the role of the Public Defender’s Office in the context of penal execution when applied to homeless individuals. The research intends to investigate the incongruity between punishment and protection in light of human dignity, the guarantees ensured by the Constitution, and social vulnerability. The study was based on a literature review and analysis of legal documents, which provided support for the theoretical debate. It was found that the Public Defender’s Office possesses competence and potential regarding punitive practices and to be effective in relation to human rights, especially those of homeless individuals; however, it is necessary to overcome the structural limitations that reduce its performance. It is up to everyone—the State, civil society, and educational institutions—to promote reflections and practices that can lead to social justice. DOI: https://doi.org/10.56238/sevened2026.008-011